RETRACTED ARTICLE: Serum melatonin levels and in a sample of Iranian patients with migraine - Mansoureh Togha; Morvarid Noormohammadi; Zeinab Ghorbani; Fariba Karimzadeh; S. Zahra Bathaie (Scientific Reports)
Abstract Migraine, a complex disorder, is characterized by recurrent headache episodes. The production of melatonin in the pineal gland, which is crucial for controlling circadian rhythms and sleep–wake cycles, is altered in various conditions, including neurological disorders such as migraine. Recent studies underscore the significance of serum melatonin levels in patients with chronic and episodic migraine, the focus of this study. This case‒control study, conducted from September 2017 to June 2020 in Tehran, Iran, selected potential participants aged 18–65 years from a headache clinic at Sina Hospital (affiliated with Tehran University of Medical Sciences). Both episodic migraine and chronic migraine were diagnosed following the diagnostic criteria in the International Classification of Headache Disorders’ third edition. Melatonin levels were measured according to the instructions of the ELISA kits. There were significant differences in the frequency of headache days and the duration of abortive medication usage between the two groups (P value < 0.001). Besides, analysis revealed significantly lower serum melatonin levels in patients with episodic ((80.45–45.06) 72.83) and chronic migraine ((154.34–63.34) 70.38, P value < 0.001) than in healthy controls (281.25–160.86) 280). Although no considerable differences were found between episodic and chronic migraine patients, the current study demonstrated that serum melatonin levels were substantially greater in healthy controls than in patients with migraine.